(untitled) (Architecture Image Studies, 2025)
Nowadays, to meet the demands of social development, the talent cultivation goals of universities have gradually shifted from the "massive training of skilled talents" in the industrial era to "personalized and innovative talent cultivation" in the intelligent era. The core goal of university education has also shifted from the traditional acquisition of knowledge and skills to the cultivation and improvement of students’ deep learning abilities.Therefore, promoting deep learning among learners is an important direction for the reform of higher education. During the crucial period of rapid development of higher education and transformation of university teaching, smart classrooms have flourished and have been endowed with more educational missions and higher value expectations. However, multiple factors need to work together to achieve deep learning. This paper adopts the quantitative research method and conducts a detailed study from three aspects: teaching environment, teachers, and teaching strategies. It explores whether the smart classroom can promote students’ deep learning compared to traditional classrooms, as well as the influence of teachers and teaching strategies on deep learning. Research has shown that smart classroom, teachers, and teaching strategies all have a significant positive impact on students’ deep learning. Based on it, this paper briefly discusses the specific aspects of each influencing factor, providing a reference for universities and teachers in the information age on how to effectively enhance students’ deep learning.